Penerapan media berbasis ICT (information and communicatiuon technologies) dalam pembelajaran matematika di MTs Al-Jam’iyatul Wasliyah Tembung - Nasution, Hafizd Darmawan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study is motivated by the advancement of technology in the field of education and its application in learning. The technology is expected to aid teachers in the teaching and learning process. This type of research is referred to as descriptive qualitative research. This data research method includes observation, interviews, documentation, and field notes. The researchers discovered that the use of ICT-based media (Information and Communication Technologies) in learning mathematics at MTs Al-Jam’iyatul Wasliyah in the 2018/2019 academic year. (1) Laptops, projectors, and speakers are examples of ICT media used in education. ICT as a learning tool is beneficial, and the applications used by teachers are effective. (2) Following the implementation of ICT-based media in learning, the teacher’s response is very effective in achieving student competencies and assisting the learning process. The responses of the students were very interesting, good, and clear in learning mathematics.